JUSTICE AND VIRTUE IN THE QUR'AN: A THEMATIC STUDY OF THE CORRELATION OF ISLAMIC SOCIAL ETHICAL VALUES - Farihah, Anis; Khoiri (PT. Antis International Publisher, 2025)
Objective: This article aims to explore the correlation between justice (‘adl) and virtue (ihsan) in the Qur'an as principles of social ethics in Islam. Method: Through a thematic exegesis (maudhu’i) approach, this study gathers verses that include both concepts to analyze their linguistic meanings and practical implementation. Results: The study finds that justice is the minimum ethical foundation that must be upheld, while ihsan represents the highest form of ethical practice that surpasses justice. Novelty: This article emphasizes that the combination of justice and ihsan serves as the main pillar in building a harmonious and civilized society.